Pengaruh work – life balance dan kepuasan kerja terhadap kinerja karyawan PT. ABC Kota Malang - Johanes Mulia; Priyo Sudibyo; Any Rustia Dewi (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2024)
Employee performance is one of the main references for entrepreneurs/companies in finding formulations that can increase the profitability of the business entity. The aim of this research is to determine the influence of Work - Life Balance and Job Satisfaction on Employee Performance at PT. ABC Malang. The sampling technique used in this research was random sampling technique. From there, a sample size of 100 employees was obtained. The data collection technique used is by using a questionnaire, using the Google Form facility. Data analysis techniques used in this research include: Variable Validity Test, then Cronbach Alpha Reliability Test, and Classic Assumption Test (Normality Test Multicollinearity Test), as well as Multiple Linear Regression Analysis. To test the hypothesis, this research uses the Simultaneous Test (Test Simultaneously) and Partial Test (T Test), as well as the Coefficient of Determination Test, using SPSS. Multiple Linear Equation Y = 6.905 + 0.284X1 + 0.387X2 + e. Based on the results of the regression test carried out by the author, the author will conclude that each variable used by the author, namely Work-Life Balance (X1), has a partial and positive influence on the Performance (Y) of Employees at PT. ABC of Malang city. Meanwhile, the variable Job Satisfaction (X2) of employees at PT ABC Malang city also has a partial and positive effect on employee performance (Y). Simultaneously, Work-Life Balance and Job Satisfaction also have a positive effect on employee performance. Coefficient of Determination Test Results R Where the results are at the point 0.511. It can be concluded that the independent variable used contributed 51.1% to this research. The Job Satisfaction variable has a dominant influence in the research. It is proven that tcount ttable, namely 6.906 1.985. Meanwhile, for the Work-Life Balance variable, the tcount is 4.395, which is greater than the ttable, namely 1.985.